Assessment of Groundwater Quality around a Cement Factory in Ewekoro, Ogun State, Southwest Nigeria - David, A. O.; Opafola, O. T.; Akisanya, O. O.; Olawomo, D. O.; Kadir, D. A. (NIU Journal of Social Sciences, 2024)
Samples of groundwater from hand dug wells and boreholes in Ewekoro, Ogun State and its environs were collected and analysed for various physicochemical parameters and some metal ions such as lead, copper, iron, manganese and zinc. Also, an independent sample test of the wells and boreholes close to the Cement Factory around that area was carried out. The qualities of groundwater were determined by investigative study which involved the determination of some heavy metals and physicochemical properties in drinking water samples. Eight (8) samples of ground water were collected from the eight sampling sites. The samples were analysed for the following parameters; iron, copper, manganese, zinc, lead, color, dissolved solids, electrical conductivity, pH, dissolved oxygen (DO), biological oxygen demand (BOD), chemical oxygen demand (COD), temperature, turbidity and total hardness using standard methods. The test results showed the variation of the investigated parameters in the samples as follows: temperature 26-31 o C, pH 5.9-7.2, electrical conductivity (EC) 0.37 – 0.78 µS/cm, total hardness 181.8 – 333.0 mg/l, turbidity 0.00-0.05 FTU, colour 5-10 TCU, dissolved oxygen 4.31-5.01 mg/l, BOD 0.2-1.0 mg/l, COD 2.0 -4.0 mg/l, Cu 0.04 – 0.09 mg/l, Fe 0.006-0.122 mg/l, Zn 0.016-0.306 mg/l, Mn 0.01-0.05 mg/l and Pb < 0.001 mg/l. The concentrations of some of the investigated parameters in the drinking water samples from the research region were above the permissible limits of the World Health Organization standard for drinking water quality guidelines. The dissolved oxygen was found to exceed 5.0 mg/l which is the WHO permissible limit, Also Limestone was found to exceed the WHO maximum limit of 170 mg/l. All the above results confirmed the high pollution of the ground water sources and hence, they are not suitable for consumption without any prior treatment. Keywords: Groundwater, Quality, Heavy metals, parameters.